Ways to Reduce Consumer Complaints – the EU Perspective - Cătălina Soriana Sitnikov; Claudiu George Bocean (Amfiteatru Economic)
Organizations are currently concerned with meeting consumers’ demands and needs by creating products that meet their expectations. Addressing wider issues of consumers’ protection and relying on a detailed research of the latest data from the European Union, our paper analyses and synthesizes ways to reduce consumers’ complaints on products and services purchased, based on a series of causal links and interrelated activities. It is a dual approach in order to link quantitative and qualitative arguments as well as the analysis of correlations between efforts and the recorded effects in the domain of the consumer’ protection. Based on data provided by the Flash Eurobarometer 332 there were determined the existing influences in consumers’ protection, calculating correlations among a number of indicators registered in the European Union in the field of consumer protection. Based on the relations established between the indicators that describe the domain of the protection of consumer, a model that centres on complaining in case of problems, indicating the main ways to reduce these complaints was developed and built.